Application of Activated Carbon Mixed Matrix Membrane for Oxygen Purification - Tutuk Djoko Kusworo; Ahmad Fauzi Ismail; Ahmad Mustafa; , Budiyono (International Journal of Science and Engineering, 2010)
This study is performed primarily to investigate the effect of activated carbon on oxygen separation performance of polyethersulfone mixed matrix membrane. In this study, polyethersulfone (PES)-activated carbon (AC) mixed matrix membranes were fabricated using dry/wet technique. This study investigates the effect of polyethersulfone concentration and activated carbon loading on the performance of mixed matrix membrane in terms of permeability and selectivity of O2/N2 gas separation. The fabricated flat sheet mixed matrix membranes were characterized using permeation test, Field Emission Scanning Electron Microscopy (FESEM) analysis and Differential Scanning Calorimetry (DSC). It was found that the activated carbon loading affected the gas separation performance of mixed matrix membrane. PES- 1wt% AC membrane yielded 3.75 of O2/N2 selectivity, however 5 wt% of AC can produced 5 O2/N2 selectivity